Expression of Blimp-1 transcription factor mRNA isoforms in the mononuclear cells from bone marrow of leukemia and lymphoma patients - Kaewrakmuk, Jedsada; Laomanit, Laddawan; Punyot, Mongkol; Charoenkwan, Pimlak; Nawarawong, Weerasak; Petsophonsakul, Wilaiwan (Biomedical Sciences and Clinical Medicine, 2024)
Objective To determine the expression of Blimp-1 mRNA isoforms in the mononuclear cells from bone marrow of patients with leukemia and lymphoma. Method Twenty three bone marrow samples were obtained from leukemia or lymphoma patients at Maharaj Nakorn Chiang Mai University Hospital. Bone marrow mononuclear cells were isolated by Ficoll-Hypaque gradient centrifugation. The expression of full length and exon 7 deleted (Δ7 isoform) mRNA was performed by RT-PCR. The Molecular Analysis program was used to analyze intensity of the PCR products. The band intensity ratio of Blimp-1 isoforms was compared with the GAPDH control of the same sample. Results Blimp-1 mRNA isoforms were found to have abnormal expressions in some patients. Most patients who expressed both isoforms presented more Δ7 isoforms than full length ones, whereas of four patients; two with ALL, one with AML and one with lymphoma, were found to have the opposite ratio. Only Δ7 isoform was expressed in 2 patients with NHL, who were both new cases of untreated patients. Interestingly, one abnormal isoform with an unusual PCR product size of 1,150 bp was found in a patient with ALL. This patient also showed an abnormal expression of XBP-1, a downstream signaling of Blimp-1 that responds to ER stress and is involved in immunoglobulin secretion. Conclusion This study demonstrated the expression profile of full-length and Δ7 Blimp-1 isoforms in primary leukemic and lymphoma cells. One isoform, which has not been described, was identified in one patient diagnosed with ALL. As Δ7 isoforms lack a DNA binding domain, an abnormally high level of Δ7 isoform expression may play a role in the malignant transformation of these cells.